Disparitas Antar Wilayah Dan Provinsi Di Indonesia Sebelum dan Sesudah Otonomi Daerah - ., Yanuar (Jurnal Ekonomi, 2013)
Since the application of local autonomy in Indonesia in 2001, there have been more opportunities for the local governments to organize and manage their regions. It is meant to achieve regional development targets in improving the people's welfare and quality of life in accordance with eac region's and provinces in Indonesia before and after the application of local autonomy. It used the descriptive mertod with secondary data from 1991 up to 2010, and the Gini coeffient analys. This survey has concluded that the application of local autonomy have remained high,both among the regional and provincial levels. During the period of conducting this research, the local autonomy has not signitificantly secceedeed in reducing the desparity levels among regions and provinces in Indonesia.